Peace Education sebagai Resolusi Konflik Studi Kasus di Forum Persaudaraan Umat Beriman (FPUB) DIY - Imam Machali; Zainal Arifin; Ahmad Rodli (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2015)
This article describes a peace education, as conflict resolution and other forms of conflict resolution based on religiousconducted by FPUB in Yogyakarta. The results showed that the activity FPUB in conflict resolution is carried out through four forms, namely; First, discussions and inter-religious dialogue is a cultural movement that is trying to explore, understand, and mutual understanding of the real problems faced by the community. Secondly, social solidarity that concern the political situation, social, economic, and cultural. Thirdly, peaceful action and prayer together. Fourth, peace education is the process of accepting and respecting differences as a form of de-radicalization and conflict resolution in order to build inter-religious relations are open, egalitarian and peaceful. Forms of peace education are peace and non-violence, human rights, democracy, tolerance, international and intercultural understanding, and cultural and linguistic diversity